Endoscopic Septoplasty Methods in Modern Interpretation - Ergashevich, Qiyomov Ikhtiyor (Journal of Science in Medicine and Life, 2024)
The role of the nasal septum in the functioning of the nose and its paranasal sinuses is invaluable. Many people cannot boast of a perfectly straight nasal septum, although it is often slightly bent and the defect is not considered a pathology. There are people with a pronounced curvature of the nasal septum.